Un ensayo comparativo sobre condiciones locales de producción y lógicas mundializadas de posibilidad (del café en la sierra hidalguense al aceite de oliva en Andalucia) - Palacios Ramírez, José (Nómadas. Critical Journal of Social and Juridical Sciences, 2007)
The central idea of this paper is to present two ethnographic examples of the interactions between the different levels of the socio-economic worldwide realities. This paper proposes a comparative view based in two ethnographic examples of agribusiness production very different at first sight, but with some structural similarities, almost as interesting as its differences. The examples will be, on one side, a Mexican region dedicated to the coffee production, and on the other, a Spanish locality dedicated to the olive exploitation and the production of olive oil.